Determinants of fertility levels in Kafanchan, Nigeria - D. O. Ogbonnas; M. Mamman (Faculty of Geography, Universitas Gadjah Mada, 1990)
This study is an attempt to investigate the general level of fertility in Kafanchan, a town in Kaduna State of Nigeria: The main concern is to examine the individual and group behaviour of the population with specific reference to the prevailing fertility rates.The paper examines some of socio-cultural factors that relate to fertility history, attitude related to fertility and knowledge and use of contraception.On the average, fertility in this community is high. A woman experiences a total life time fertility of 7 live-births and least one of the children die in childhood. Marriage is universal and every young man and woman aspires to satisfy this social obligation. The mean age at marriage is 17 years. A lot of importance is attached to having children, for social and cultural reasons. Knowledge and use of contraception is still very low. Government interest in population matters has been mainly restricted to population data collection for the purpose of soda- economic and political planning. These factors have a positive bearing on average family size which is relatively large.Fertility is high while mortality is low. However, as a measure towards demographic readjustment, a further reduction in the level of mortality may lead to decline in fertility. Some future planning implications of the existing fertility' evels are discussed in the light of the current population policy and development planning in the country.